Sintered neodymium-iron-boron magnet and preparation method and application thereof
By increasing the content of B element in the thin neodymium iron boron magnet and using multiple low-temperature diffusion techniques, the problem of excessive diffusion of heavy rare earth elements is solved, and the coercivity and squareness of the magnet are improved.
Patent Information
- Application Number
- CN202510134375.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-07
AI Technical Summary
When preparing thin-sheet NdFeB magnets, heavy rare earth elements diffuse excessively into the main phase, resulting in a decrease in coercive force and squareness of the magnet.
By controlling the composition and process flow of the neodymium iron boron magnet, the content of element B is increased to delay the diffusion rate of heavy rare earth elements, and multiple low-temperature diffusion techniques are used to evenly distribute heavy rare earth elements.
It effectively prevents excessive diffusion of heavy rare earth elements, improves the coercive force and squareness of the magnet, and avoids the decline of Hcj and Hk/Hcj.
Smart Images

Figure CN119601334A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth permanent magnetic materials and preparation thereof, and in particular relates to a sintered NdFeB magnet and a preparation method and application thereof. Background Art
[0002] Sintered NdFeB magnets, due to their ultra-high magnetic strength, require fewer magnets to generate the same magnetic field as a large number of other magnetic materials during application. Therefore, the use of thin-sheet NdFeB magnets can significantly reduce product volume and reduce product weight, meeting the motor industry's demand for miniaturization and lightweighting.
[0003] The grain boundary diffusion technology can improve the coercivity of NdFeB magnets while avoiding a significant decrease in remanence. It uses heavy rare earth elements (such as Dy or Tb) to diffuse along the grain boundaries of NdFeB magnets at high temperatures, thereby forming a shell structure with high coercivity at the edge of the main phase grains. This structure can effectively improve the coercivity of NdFeB magnets while avoiding a significant decrease in remanence. This process is widely used in sintered NdFeB magnets with a thickness of 2-8mm, and can produce magnets with high comprehensive magnetic properties that are difficult to achieve with traditional processes. However, for thin-film products, especially those with an oriented thickness of less than 1.3mm, it is very easy to diffuse excessively, and more heavy rare earth diffuses into the main phase. The main phase grains will form an inverse core-shell structure, and both Hcj and Hk / Hcj will be greatly reduced. Summary of the invention
[0004] In order to improve the above technical problems, the present invention provides a sintered NdFeB magnet, which comprises, by mass percentage, 100%: Re: 28-32%, Re is selected from at least one of Pr, Nd, Dy, Tb, and Ho; B:1.000%-1.080%; M: 0-5% and not 0, M includes at least Zr and / or Ti, and 0.1%<Zr+Ti≤0.2%.
[0005] According to an embodiment of the present invention, the thickness of the NdFeB magnet in the orientation direction is T≤1.3 mm, preferably, 0.6 mm≤T≤1.3 mm; examples are 0.6 mm, 0.8 mm, 1 mm, and 1.3 mm.
[0006] According to an embodiment of the present invention, 1.065%-T / 2000≤[B]≤1.065%-T / 3000; wherein [B] refers to the mass content of B, and T is the thickness of the NdFeB magnet in the orientation direction.
[0007] Preferably, when the magnet thickness is 0.6 mm, the B content is 1.035%-1.045%; When the magnet thickness is 0.8mm, the B content is 1.025%-1.038%; When the magnet thickness is 1.0mm, the B content is 1.015%-1.031%; When the magnet thickness is 1.3mm, the B content is 1.000%-1.021%; According to an embodiment of the present invention, the M may further include at least one of Co, Ni, Al, Cu, and Ga.
[0008] According to an embodiment of the present invention, the total content of Zr and Ti is 0.15-0.2%, for example, 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.2%.
[0009] According to an embodiment of the present invention, in the NdFeB magnet, the balance is Fe and impurities, wherein the impurities are unavoidable impurities, such as at least one of elements such as C, N, O, S, Si, and Mn.
[0010] According to an embodiment of the present invention, the composition of the NdFeB magnet, based on 100% by mass, includes Re29.0-31.5wt%, for example, 29.0%, 29.5%, 30.0%, 30.3%, 30.5%, 31.0%, and 31.5%.
[0011] According to an embodiment of the present invention, in the NdFeB magnet, Re contains at least Nd, and may also contain at least one of Pr, Dy, Tb, and Ho.
[0012] According to an embodiment of the present invention, the composition of the NdFeB magnet is 100% by mass, and the content of B is, for example, 1wt%, 1.02wt%, 1.04wt%, 1.05wt%, 1.06wt%, 1.07wt% or 1.08wt%.
[0013] Research has found that when the magnet of the present invention is subjected to grain boundary diffusion, a high content of B element can ensure the presence of an appropriate amount of boron-rich phase. During the grain boundary diffusion of the magnet of the present invention, the diffusion of heavy rare earth elements dysprosium or terbium into the interior of the magnet can be delayed, thereby effectively preventing excessive diffusion from causing a decrease in Hcj and Hk / Hcj.
[0014] According to an embodiment of the present invention, the composition of the magnet is calculated as 100% by mass, and the content of M is, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.8wt%, 1wt%, 1.5wt%, 1.8wt%, 2wt%, 2.5wt%, 2.8wt%, 3wt%, 4wt% or 5wt%.
[0015] According to an embodiment of the present invention, the difference between the content of heavy rare earth metals (such as Dy and / or Tb) on the surface and the content distributed in the center of the magnet is 0.1-0.2%.
[0016] The present invention also provides a method for manufacturing the sintered NdFeB magnet, the method comprising: The raw materials for preparing the sintered NdFeB magnet are processed through a smelting process, a powder making process, a pressing process, a heat treatment process and a diffusion process to prepare the sintered NdFeB magnet.
[0017] According to an embodiment of the present invention, in the smelting process, the raw materials are prepared according to the proportions of the components of the magnet, melted at 1300-1450° C., and rapidly cooled to form alloy sheets.
[0018] According to an embodiment of the present invention, in the powder making process, the smelted alloy flakes are made into alloy powder through HD hydrogen crushing, coarse grinding, medium grinding, first airflow grinding and second airflow grinding processes in sequence. In the present invention, the HD hydrogen crushing, coarse grinding, medium grinding and airflow grinding can all be performed by methods known in the art.
[0019] Preferably, the hydrogen absorption pressure of HD hydrogen crushing is 200 MPa.
[0020] Preferably, the particle size of the first jet milling is ≥5.0 μm, preferably, the particle size of the first jet milling is ≥5.0 μm and <7.0 μm.
[0021] Preferably, the particle size of the second jet milling is ≥3.0 μm, and preferably, the particle size of the second jet milling is ≥5.0 μm and ≤4.0 μm.
[0022] Preferably, the difference between the particle size of the first air flow milling and the particle size of the second air flow milling is ≥2.0μm. The alloy powder of the present invention is subjected to two air flow millings, so that the particle size of the first air flow milling and the particle size of the second air flow milling differ by more than 2.0μm, so that the second grinding powder is easier to break, the shape is closer to spherical, and the agglomerated impurity grain boundary phase at the grain boundary coupling is removed, so as to prevent the agglomeration and uneven diffusion of heavy rare earths during diffusion, which is beneficial to the distribution of thin layers of neodymium-rich phases, thereby ensuring the diffusion consistency and uniformity of different positions of the magnet product, and Hcj is also improved. At the same time, the neodymium-rich phase is fully nitrided, and the nitrogen content in the magnet is 600-1000ppm, which can slow down the diffusion rate and prevent the heavy rare earth from entering the main phase during diffusion.
[0023] According to an embodiment of the present invention, the first jet milling powder is sent to a cyclone separator for separation. Preferably, the first jet milling powder is sent to a first cyclone separator for separation.
[0024] According to an embodiment of the present invention, the second jet milling powder is sent to a cyclone separator for separation. Preferably, the second jet milling powder is sent to a second cyclone separator for separation.
[0025] According to an embodiment of the present invention, the cyclone separator is a cylinder and a conical barrel from top to bottom, and the cylinder and the conical barrel are connected; The top of the cylinder includes a cylinder inlet and a cylinder outlet, the cylinder inlet is used to feed airflow grinding (including the first airflow grinding or the second airflow grinding), and the cylinder outlet is used to discharge gas, and the gas contains a small amount of ultrafine powder; The bottom of the cone barrel is provided with a cone barrel outlet, and the cone barrel outlet is used to collect powder of required particle size.
[0026] Preferably, the first airflow milling and the second airflow milling steps of the powder making process are carried out in an airflow mill device, and the airflow mill device includes a first cyclone separator, a second grinding chamber and a second cyclone separator.
[0027] Preferably, the diameter of the cylinder of the cyclone separator is between 0.55-0.75 m, and the height of the cylinder is between 0.8-1.2 m.
[0028] Preferably, the height of the cone barrel of the cyclone separator is 1.0-1.4 m.
[0029] The present invention controls the recovery amount of ultrafine powder after the second air flow milling to be between 1.5-3%, wherein the ultrafine powder is the powder discharged from the top of the second cyclone separator, which can separate the agglomerated impurity grain boundary phase at the grain boundary coupling, is beneficial to the distribution of the neodymium-rich phase thin layer, and can slow down the diffusion speed of the thin sheet product, thereby avoiding over-diffusion.
[0030] According to an embodiment of the present invention, in the pressing process, the magnetic powder is oriented and pressed under an external magnetic field, and then demagnetized to obtain a block compact. Preferably, before pressing, it is necessary to carry out orientation magnetization and molding under a magnetic field strength of 1.5-2T. After pressing, a reverse magnetic field of 1.8-2T is applied for demagnetization. Preferably, the density of the block compact is 4-4.5g / cm 3 .
[0031] According to an embodiment of the present invention, after the pressing process and before the heat treatment process, the block compact can be subjected to isostatic pressing, which can increase the compact density and improve the qualified rate of subsequent sintered products.
[0032] Preferably, the pressure and time of the isostatic pressing treatment can be carried out using techniques known in the art, for example, the isostatic pressing treatment is carried out at 170 MPa.
[0033] According to an embodiment of the present invention, in the heat treatment process, the green compact obtained in the pressing process is sintered and aged in an inert gas atmosphere to obtain a NdFeB blank. Preferably, the inert gas is selected from nitrogen, argon, helium, etc.
[0034] According to an embodiment of the present invention, the sintering temperature is 1000-1100° C., and the sintering time is 4-10 h.
[0035] According to an embodiment of the present invention, the aging treatment includes a first aging process and / or a second aging process; The first aging process includes: a treatment temperature of 600-750°C; a treatment time of 4-10h; The second aging process includes: a treatment temperature of 500-650° C.; and a treatment time of 4-10 hours.
[0036] According to an embodiment of the present invention, after the heat treatment process, the sintered product may be processed into a sheet with a thickness T of ≤1.3 mm.
[0037] Preferably, the thin slice is not subjected to double-end grinding after multi-wire cutting, but is directly subjected to the diffusion process after cleaning, such as water washing and / or alcohol washing. The surface grains and neodymium-rich phases after multi-wire cutting of the present invention are destroyed, which prevents heavy rare earth from quickly entering the grain boundary phase, and is conducive to the diffusion of the thin slice.
[0038] Preferably, before the diffusion process is performed, the prepared NdFeB magnet matrix is processed into a block with a size of 45-20-Tmm (length-width-thickness (T is the thickness of the NdFeB magnet in the orientation direction)).
[0039] Preferably, the thickness T of the NdFeB magnet in the orientation direction is T≤1.3 mm.
[0040] According to an embodiment of the present invention, the diffusion process adopts the processes and equipment commonly used in the art.
[0041] According to an embodiment of the present invention, the diffusion source uses heavy rare earth metals, such as Dy and / or Tb powder. Preferably, the heavy rare earth metal content on the surface of the product is 0.08-2wt%, for example, 0.08wt%, 0.1wt%, 0.5wt%, 1wt%, 1.5wt% or 2wt%.
[0042] According to an embodiment of the present invention, the diffusion process is: The diffusion source is covered on the surface of the NdFeB magnet substrate and heat treated.
[0043] According to an embodiment of the present invention, in the diffusion process, a first diffusion and a second diffusion treatment are used, after the second diffusion treatment is completed, the mixture is cooled to room temperature, and then a third diffusion treatment is performed; The temperature of the first diffusion is 700-800°C, and the diffusion time is 5-10h. Preferably, the diffusion temperature is, for example, 700°C, 720°C, 740°C, 750°C, 760°C, 780°C or 800°C. The temperature of the second diffusion is 800-900° C., and the diffusion time is 5-10 h. Preferably, the diffusion temperature is, for example, 800° C., 820° C., 840° C., 850° C., 860° C., 880° C. or 900° C.; The temperature of the third diffusion is 450-660°C, and the diffusion time is 5-10h. Preferably, the diffusion temperature is, for example, 450°C, 480°C, 500°C, 550°C, 560°C, 580°C, 600°C, 620°C or 660°C.
[0044] The present invention uses multiple low-temperature diffusions to allow the heavy rare earth to slowly enter the thin-sheet product more evenly and prevent diffusion into the main phase.
[0045] In the magnet of the present invention, the difference in coercive force before and after diffusion is ≥900 kA / m, and the difference in the surface content and the central distribution content of the heavy rare earth metal (such as Dy and / or Tb) after diffusion is 0.1-0.2%.
[0046] The present invention also provides the application of the magnet in the fields of motors, loudspeakers, magnetic separators, computer disk drives, magnetic resonance imaging equipment, etc.
[0047] Preferably, the magnet is used in a motor as a motor rotor magnet.
[0048] Beneficial effects of the present invention: Compared with the diffusion of conventional thin-sheet magnet products, the magnet of the present invention increases the B element content, ensures the presence of an appropriate amount of boron-rich phase, and in the process of diffusing the thin-sheet magnet, can slow down the diffusion rate of heavy rare earth dysprosium or terbium into the interior of the magnet, preventing the excessive diffusion of heavy rare earth and causing a decrease in Hcj and Hk / Hcj. In addition, a secondary airflow milling process is adopted, and the difference in particle size between the two grindings is more than 0.2μm, making the second grinding powder easier to break, the shape is closer to a sphere, and removing the agglomerated impurity grain boundary phase at the grain boundary coupling, preventing the heavy rare earth from agglomerating and diffusing unevenly during diffusion, which is beneficial to the distribution of the neodymium-rich phase thin layer, ensuring the diffusion consistency and uniformity of the magnet product at different positions, and Hcj is also improved. At the same time, the neodymium-rich phase is fully nitrided, which can slow down the diffusion rate and prevent the heavy rare earth from entering the main phase during diffusion. The method of the present invention uses multiple low-temperature diffusions to allow the heavy rare earth to slowly enter the thin-sheet product, and it can be more uniform, preventing diffusion into the main phase. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is a structural schematic diagram of the cyclone separator of the present invention. DETAILED DESCRIPTION
[0050] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0051] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0052] The raw materials were configured according to the composition table of NdFeB magnets in Table 1 (all units are wt%), and sintered NdFeB magnets were prepared by the following preparation method: The raw materials in Table 1 were put into a vacuum melting furnace and heated to 1450°C by electromagnetic induction in an Ar atmosphere to melt. The molten alloy was poured onto a polished quenching roller and cooled to obtain NdFeB quick-solidified thin sheets.
[0053] Table 1
[0054] The quick-setting flakes obtained above were subjected to hydrogen explosion treatment with a hydrogen absorption pressure of 200 MPa, followed by ball milling, followed by the first and second airflow milling processes, with the target particle size D50 of the first airflow milling being 5.0 μm and the target particle size D50 of the second airflow milling being 3.0 μm.
[0055] The first jet milling and the second jet milling process of the powder making process are carried out in a jet milling device, and the jet milling device includes a first cyclone separator (i.e. Figure 1 Separator 1), the second grinding chamber (i.e. Figure 1 Second cyclone separator (i.e. Figure 1 Separator 2).
[0056] The first grinding chamber (i.e. Figure 1 The first jet mill powder obtained by medium grinding 1) is sent to the first cyclone separator (or cyclone separator 1) for separation; The second air flow grinding is sent to the second cyclone separator (or cyclone separator 2 or Figure 1 The separation is carried out in the separator 2).
[0057] The cyclone separator is composed of a cylinder and a conical barrel from top to bottom, the cylinder and the conical barrel are connected, the top of the cylinder includes a cylinder inlet and a cylinder outlet, the cylinder inlet is used to feed air flow grinding powder, and the cylinder outlet is used to discharge gas, and the gas contains a small amount of ultrafine powder; The bottom of the cone barrel is provided with a cone barrel outlet, and the cone barrel outlet is used to collect powder of required particle size.
[0058] From cyclone separator 1 (i.e. Figure 1 The powder collected at the cone outlet of the separator 1) is then fed to the second grinding chamber (i.e. Figure 1 Medium grinding 2) After grinding, the second air flow milling powder is obtained.
[0059] By controlling the diameter of the cylinder of the cyclone separator at 0.6m, the height of the cylinder at 0.9m, and the height of the cone barrel at 1.1m, the recovery of ultrafine powder after the second air flow milling is controlled at 2%. The above-mentioned air flow milled powder is filled into the vacuum press mold, oriented and pressed in a magnetic field with a magnetic field strength of 2T, and then isostatically pressed at 170MPa to obtain a compact. The above-mentioned compact is placed in a vacuum sintering furnace, heated to 1070℃ at a rate of 5℃ / min, sintered at a controlled sintering temperature of 1070℃, sintered for 5h, and treated at an aging temperature of 510℃ for 5h to obtain the NdFeB magnet blank of this embodiment.
[0060] The NdFeB magnet blanks of Examples 1-5 and Comparative Examples 1-6 were processed into NdFeB magnet black sheets of 45 mm, 20 mm in width and thickness as shown in Table 1, denoted as M1 to M11. The heavy rare earth content of the NdFeB magnet black sheets M1 to M11 was measured, denoted as RH1 to RH11.
[0061] The magnetic properties / squareness of the NdFeB magnet black sheets of Examples 1-5 and Comparative Examples 1-6 were tested and recorded as H1 / F1, H2 / F2...H111 / F11.
[0062] The above-mentioned NdFeB magnet black sheet is not subjected to any grinding treatment, but only water washing treatment is adopted for 10 minutes, and then diffusion treatment is carried out. The specific diffusion treatment method is: after attaching 0.9wt% Tb (coating method is used in this embodiment), a secondary grain boundary diffusion treatment of 750℃&10h+880&10h is carried out, cooled to room temperature, and then heated to 550℃ and kept for 5h for diffusion aging treatment (i.e., the third diffusion), and high remanence and high coercivity magnets M1'~M11' after diffusion treatment are obtained. The heavy rare earth content of NdFeB magnets M1'~M11' is measured, recorded as RH1'~RH11'.
[0063] The magnetic properties / squareness of the NdFeB magnet black sheets of Examples 1-5 and Comparative Examples 1-6 were tested and recorded as H'1 / F'1, H'2 / F'2...H'11 / F'11.
[0064] The test method (1) Method for measuring the difference in heavy rare earth: first grind the product after diffusion to 0.03mm in thickness direction, then process three adjacent sample columns of 2&2&T in length, width and thickness direction of the product, T is the product thickness, marked as sample columns A, B and C respectively, take sample column A and grind to 0.3mm along the T direction, take sample column B and grind to 0.15mm on both sides of the T direction, and do not process sample column C, and use a spectrometer to test the heavy rare earth content RH(A), RH(B) and RH(C) in full dissolution. The difference in heavy rare earth △RH=(RH(C)×T-RH(B×(T-0.3)) / 0.3-RH(A), and the difference in heavy rare earth refers to the difference between the heavy rare earth content of 0.15mm on both sides of the surface of the product along the T direction and the heavy rare earth content of 0.3mm in the center.
[0065] (2) Method for measuring magnetic energy: First grind the diffused product by 0.03 mm in thickness direction, then process n adjacent sample columns of 7&7&T in length, width and thickness direction of the product, 3.8 / T<n<4.4 / T, and align and stack the n sample columns along the thickness direction to test the magnetic properties.
[0066] (3) Squareness measurement method: The method is the same as (2). First, grind the diffused product in the thickness direction by 0.03 mm. Then, process n adjacent sample columns of 7&7&T in the length, width and thickness directions of the product. 3.8 / T<n<4.4 / T. The n sample columns are aligned and stacked in the thickness direction to test the squareness.
[0067] The test results are shown in Table 2 below.
[0068] Table 2
[0069] in conclusion: The difference between Examples 1 and 2 and Comparative Example 6 is that Examples 1 and 2 contain Ti\Zr, and 0.1%<Zr+Ti≤0.2%, and the content of Ti and Zr in Comparative Example 6 is 0.1%. The test results show that △H and △F of Examples 1 and 2 are higher than those of Comparative Example 6. It can be seen that Ti and / or Zr elements can improve the Hcj and squareness of the magnet within the scope of the present invention.
[0070] Studies have shown that when Ti is added to a magnet, the Ti element is mainly evenly dispersed in the form of Ti compounds at the triple point of the grain boundary, which plays a role in preventing grain growth. When Zr is added to a magnet, the Zr element is mainly distributed in the intercrystalline position, and forms non-magnetic particles to inhibit grain growth. The content of Ti and / or Zr in the magnet of the present invention is greater than 0.1%, so that in the diffusion process of the thin-film magnet, over-diffusion can be effectively prevented, that is, the diffusion materials Dy, Tb, etc. enter the main phase to form an inverse core-shell structure, preventing Hcj and Hk / Hcj from being greatly reduced. At the same time, the content of Ti or Zr in the magnet cannot be greater than 0.2%. It is within the range of 0.1-0.2% (not 0.1%) to significantly improve the squareness of the magnet.
[0071] The differences between Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, Example 3 and Comparative Example 3, Example 4 and Comparative Example 4, and Example 5 and Comparative Example 5 are that the B content is different. The B change in the example satisfies 1.065%-T / 2000≤[B]≤1.065%-T / 3000. The test results show that △Hcj and △F in the example are higher than those in the comparative example. It can be seen that a high content of B element can ensure the presence of an appropriate amount of boron-rich phase. In the process of diffusing the thin sheet magnet, it can delay the diffusion of heavy rare earth dysprosium or terbium into the interior of the magnet, thereby preventing excessive diffusion from causing a decrease in Hcj and Hk / Hcj.
[0072] Example 6 and Comparative Examples 7-8 Example 6 and Comparative Examples 7-8: The raw materials were configured according to the composition table of the NdFeB material of Example 1 in Table 1 (all in wt%), and sintered NdFeB magnets were prepared by the preparation method of Example 1. The difference is that: In the jet milling stage, In Example 6, the particle size of the first air flow milling was 6.0 μm, and the particle size of the second air flow milling was 3.5 μm. The difference between the two air flow millings was 2.5 μm.
[0073] In Comparative Example 7, the jet milling was performed only once, and the particle size of the jet milling was 3.5 μm.
[0074] In Comparative Example 8, the particle size of the first air flow milling was 4.0 μm, and the particle size of the second air flow milling was 3.5 μm, and the difference between the two air flow millings was less than 2.0 μm.
[0075] The process differences between Example 6 and Comparative Examples 7-8 are shown in Table 3 below.
[0076] Table 3
[0077] The magnetic properties test results of the magnets prepared in Example 6 and Comparative Examples 7-8 are shown in Table 4 below.
[0078] Table 4
[0079] in conclusion: By comparing Examples 1, 6 and Comparative Examples 7-8, it can be seen that the present invention uses two airflow mills and the particle size of the first airflow milling and the second airflow milling differs by more than 2.0 μm, making the second grinding powder easier to break and closer to a spherical shape, and removing part of the impurity grain boundary phases at the grain boundary coupling, preventing the agglomeration and uneven diffusion of heavy rare earth during diffusion, which is beneficial to the distribution of the neodymium-rich phase thin layer, thereby ensuring the diffusion consistency and uniformity of different positions of the thin-film product, and Hcj is also improved. At the same time, the neodymium-rich phase is fully nitrided, and the nitrogen content in the magnet is 600-1000ppm, which can slow down the diffusion rate and prevent the heavy rare earth from entering the main phase during diffusion.
[0080] The raw materials were configured according to the composition table of NdFeB materials in Example 1 in Table 1 (in units of wt%), and sintered NdFeB magnets were prepared by the preparation method of Example 1, except that the height and diameter of the second airflow mill cyclone separator were different, resulting in different final ultrafine powder recovery amounts, as shown in Table 5. The properties of the prepared magnets are shown in Table 6.
[0081] Table 5
[0082] Table 6
[0083] in conclusion: By comparing Examples 1, 7 and Comparative Examples 9-10, it can be seen that the diameter of the secondary air flow mill cyclone separator is between 0.55-0.75m, the cylinder height is between 0.8-1.2m, and the cone barrel height is between 1.0-1.4m. The ultrafine powder recovery amount after the second air flow mill can be controlled between 1.5-3%, and the agglomerated impurity grain boundary phase at the grain boundary coupling can be separated, which is beneficial to the distribution of the neodymium-rich phase thin layer, and can slow down the diffusion rate of the thin film product, thereby avoiding over-diffusion.
[0084] Example 8 and Comparative Examples 11-12 The raw materials were configured according to the composition table of NdFeB materials in Example 1 in Table 1 (all units are wt%), and sintered NdFeB magnets were prepared by the preparation method of Example 1, except for the difference shown in Table 7; the properties of the prepared magnets are shown in Table 8 below.
[0085] Table 7
[0086] Table 8
[0087] in conclusion: By comparing Examples 1 and 8 with Comparative Examples 11-12, it can be seen that two low-temperature diffusions can allow the heavy rare earth to slowly enter the thin-sheet product more evenly, thereby preventing over-diffusion from causing a decrease in coercivity and squareness.
[0088] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A sintered NdFeB magnet, characterized in that: Taking mass percentage as 100%, it comprises: Re: 28-32%, Re is selected from at least one of Pr, Nd, Dy, Tb, and Ho; B:1.000%-1.080%; M: 0-5% and not 0, M at least includes Zr and / or Ti, and 0.1%<Zr+Ti≤0.2%; The thickness T of the NdFeB magnet in the orientation direction is less than or equal to 1.3 mm.
2. The magnet according to claim 1, characterized in that 1.065%-T / 2000≤[B]≤1.065%-T / 3000; wherein [B] refers to the mass content of B, and T is the thickness of the NdFeB magnet in the orientation direction.
3. The magnet according to claim 1, characterized in that When the magnet thickness is 0.6mm, the B content is 1.035%-1.045%; When the magnet thickness is 0.8mm, the B content is 1.025%-1.038%; When the magnet thickness is 1.0mm, the B content is 1.015%-1.031%; When the magnet thickness is 1.3mm, the B content is 1.000%-1.021%.
4. The magnet according to claim 1, characterized in that The M further comprises at least one of Co, Ni, Al, Cu and Ga; In the magnet, the remainder is Fe and impurities.
5. The method for preparing a magnet according to any one of claims 1 to 4, characterized in that: The method comprises: The raw materials for preparing the sintered NdFeB magnet are processed through a smelting process, a powder making process, a pressing process, a heat treatment process and a diffusion process to prepare the sintered NdFeB magnet.
6. The method according to claim 5, characterized in that In the powder making process, the smelted alloy flakes are made into alloy powder through HD hydrogen crushing, coarse grinding, medium grinding, first jet milling and second jet milling processes in sequence; And / or, the particle size of the first air jet milling is ≥5.0 μm, the particle size of the second air jet milling is ≥3.0 μm, and the difference between the particle size of the first air jet milling and the particle size of the second air jet milling is ≥2.0 μm.
7. The method according to claim 6, characterized in that The first jet milling powder is sent to a cyclone separator for separation; and / or, sending the second air flow milling powder into a cyclone separator for separation; And / or, the cyclone separator is a cylinder and a conical barrel from top to bottom, and the cylinder and the conical barrel are connected; The top of the cylinder includes a cylinder inlet and a cylinder outlet, the cylinder inlet is used to feed airflow grinding powder, and the cylinder outlet is used to discharge gas; The bottom of the cone barrel is provided with a cone barrel outlet, and the cone barrel outlet is used to collect powder of required particle size; and / or, the diameter of the cylinder of the cyclone separator is between 0.55-0.75 m, and the height of the cylinder is between 0.8-1.2 m; And / or, the height of the cone barrel of the cyclone separator is 1.0-1.4m; And / or, the recovery of ultrafine powder after air jet milling is 1.5-3%.
8. The method according to claim 6, characterized in that The diffusion process is as follows: The diffusion source is covered on the surface of the NdFeB magnet substrate and heat treated.
9. The method according to claim 8, characterized in that In the diffusion process, the first diffusion and the second diffusion treatment are adopted, and after the second diffusion treatment is completed, the temperature is cooled to room temperature, and then the third diffusion treatment is carried out; The temperature of the first diffusion is 700-800°C and the diffusion time is 5-10h; The temperature of the second diffusion is 800-900°C and the diffusion time is 5-10h; The temperature of the third diffusion is 450-660°C and the diffusion time is 5-10h.
10. Use of the magnet according to any one of claims 1 to 4 in the fields of motors, loudspeakers, magnetic separators, computer disk drives or magnetic resonance imaging equipment.
Citation Information
Patent Citations
R-T-B magnet material, preparation method and application thereof
CN111210987A
Preparation method of neodymium-iron-boron magnetic material
CN113096952A
Sintered neodymium-iron-boron magnet and preparation method thereof
CN115863039A
High-residual-magnetism high-coercive-force neodymium-iron-boron magnet and preparation method thereof
CN119132777A
Method and equipment for pulverizing permanent-magnet rare-earth NdFeB alloy
CN1390664A